2021
DOI: 10.3389/fsoc.2020.612559
|View full text |Cite
|
Sign up to set email alerts
|

The Italian Deaf Community at the Time of Coronavirus

Abstract: The present paper will explore the impacts of the recent pandemic crisis on the Italian Deaf community, as a linguistic minority. Recent research has shown that minorities are suffering much more the effects of the pandemia because their lack of access to services and in a much wider perspective, to education and welfare. We will show that, during the COVID crisis, despite lockdown measures, various actions at the formal political level (from the Italian Deaf Association) and at the informal level (from the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Alsindi et al [ 77 ] highlighted that in addition to miscommunication between teacher and student, the lack of interpreter’s knowledge regarding art and design hindered the performance of students. Deaf students have also suffered from a lack of access to education and welfare services, such as inadequate sign language interpreting avenues, the difficulty of lip-reading when teachers are wearing masks, limited direct support by teachers, among others [ 58 , 78 – 80 ]. Unfortunately, the COVID-19 pandemic has worsened social exclusion among deaf students, especially with the disruption of daily interactions with other people, lack of access to information, and inadequate sign language interpreters [ 6 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alsindi et al [ 77 ] highlighted that in addition to miscommunication between teacher and student, the lack of interpreter’s knowledge regarding art and design hindered the performance of students. Deaf students have also suffered from a lack of access to education and welfare services, such as inadequate sign language interpreting avenues, the difficulty of lip-reading when teachers are wearing masks, limited direct support by teachers, among others [ 58 , 78 – 80 ]. Unfortunately, the COVID-19 pandemic has worsened social exclusion among deaf students, especially with the disruption of daily interactions with other people, lack of access to information, and inadequate sign language interpreters [ 6 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also recommended that parents look for suitable online educational programs, find opportunities for exposure to deaf students, communicate with deaf and hard-of-hearing students, enable deaf and hard-of-hearing students to socialize, and assist them in getting the services they need [ 92 ]. A combination of government-led and community-led responses has also provided greater educational and social support for deaf students [ 78 ]. It is also proposed that recognition of group rights will lead to greater inclusion for deaf students, so that cultural and linguistic accessibility can be offered to the population [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Paatsch and Toe [36] utilized a literature review methodology and indicated that DHH students in typical classrooms developed pragmatic skills and proposed using the conversation model to deal with the challenges faced by such students. Finally, Tomasuolo et al [37] conducted exploratory research in Italy and found that initiatives at the political and informal level promoted sign language and assisted in DHH education during the pandemic.…”
Section: Deaf Students During Covid-19 Studiesmentioning
confidence: 99%
“…From the related work, there is no study addressing online learning for deaf students in Saudi Arabia, which is the focus of the current study. [44] Identifying online learning practices make social inclusion Literature review N/A N/A N/A N/A possible for individuals with disabilities Alcazar et al [38] Creating a supplementary English elearning system made Survey Philippine Institute Students, N/A Philippines for the Deaf of the Deaf Teachers McKeown [45] Proposing a model which describes the three barriers deaf Literature review N/A N/A N/A N/A students might encounter in an online learning situation Batanero et al [39] Testing a redesign of the Moodle platform on deaf and Empirical study Moodle platform Students 23 N/A deaf-blind students Exploring current trends in online higher education, data on Counselman et al [46] the experience of Deaf/deaf/Hard of Hearing students and Literature review N/A N/A N/A N/A current options for improving inclusively in the online classroom Fernandes et al [33] Examining how the education of voters for deaf people Interview GERKATIN Students 33 Indonesia Lynn et al [34] Identifying Successes and challenges in teaching chemistry Author's insights NTID N/A N/A United States Tomasuolo et al [37] Exploring the impacts of the recent pandemic crisis Exploratory research Literature review N/A N/A Italy Smith and Colton [30] Developing a YouTube channel that focuses on providing Literature review Author's experience N/A N/A United States Alsadoon and Turkestani [4] Identifying the lecturers' obstacles during virtual classroom Interview King Saud University lecturers 11 Saudi Arabia Kritzer and Smith [29] Recommending…”
Section: Deaf Students In Online Learningmentioning
confidence: 99%